Investigation on mechanisms of current saturation in gateless AlGaN/GaN heterostructure device. (4th February 2021) - Tao, Qianqian; Wang, Jinyan; Bin Zhang; Wang, Xin; Li, Mengjun; Cao, Qirui; Wu, Wengang; Ma, Xiaohua
Abstract: The current saturation in a gateless AlGaN/GaN heterostructure device is investigated in this letter. Analysis of the micro-Raman spectroscopy results indicated that the self-heating effect could be eliminated by the 10  μ s pulse measurement. Based on the proposed multi-probe gateless AlGaN/GaN heterostructure device, the uniform channel depletion is experimentally verified even in the case of current saturation. The pre-stress measurement and transient current measurement results suggest that the surface traps with an extracted surface trap energy level of 0.13 eV are uniformly charged along the channel. Furthermore, a forward electron injection explanation is proposed and confirmed by TCAD simulation.